PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN INQUIRY DENGAN MEDIA GAMBAR - Diah Sudiarti (FKIP Universitas Islam Jember, 2016)
Inquiry learning is learning or review for problem solving in a critical, analytical, and scientific used particular steps. Media is physical tool that can stimulate students to learn. Learning activities are the students’ activities in the learning process through from physical activities to psychological activities. This research aimed to increase the students’ learning activities using Inquiry learning model and image media. The research design used was Classroom Action Research (CAR), with qualitative descriptive approach. Based on the result of research, indicated that there were 43,2% of student learning activity on the first cycle and 86% on the second cycle. While in the learning outcomes of students on the first cycle showed 70% and 88% on the second cycle. As the basis of the research findings, the activity and student learning outcomes can be increased through the Inquiry model with the image media. Keywords: Image Media, Learning Activity, Learning Inquiry, learning outcomes